2017
DOI: 10.1007/s00228-017-2347-7
|View full text |Cite
|
Sign up to set email alerts
|

Sequential versus concomitant therapy for treatment of Helicobacter pylori infection: an updated systematic review and meta-analysis

Abstract: The efficacy of concomitant therapy was duration dependent, and 10-day concomitant therapy was superior to 10-day sequential therapy. Compared to sequential therapy, concomitant therapy was more efficacious for metronidazole-resistant strains and metronidazole plus clarithromycin-resistant strains. However, diarrhea was more frequent with concomitant therapy than with sequential therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 56 publications
3
19
1
Order By: Relevance
“…A sub-analysis linking outcomes with antibiotic resistance showed that the concomitant regimen performed significantly better in metronidazole-resistant strains [129]. This finding was also confirmed by a recent updated systematic review and metaanalysis comparing sequential vs. concomitant regimens [140]. In addition, in one RCT, an optimized 14-day sequential regimen containing a high dose of a second-generation PPI (esomeprazole 40 mg bid) achieved high eradication rates in both per-protocol (93.9%) and intention-to-treat (91.3%) analyses in a population that included about 20% clarithromycin resistance [141].…”
Section: Recommendation Grade: A; Evidence Level: 1b; Agreement Levelmentioning
confidence: 62%
“…A sub-analysis linking outcomes with antibiotic resistance showed that the concomitant regimen performed significantly better in metronidazole-resistant strains [129]. This finding was also confirmed by a recent updated systematic review and metaanalysis comparing sequential vs. concomitant regimens [140]. In addition, in one RCT, an optimized 14-day sequential regimen containing a high dose of a second-generation PPI (esomeprazole 40 mg bid) achieved high eradication rates in both per-protocol (93.9%) and intention-to-treat (91.3%) analyses in a population that included about 20% clarithromycin resistance [141].…”
Section: Recommendation Grade: A; Evidence Level: 1b; Agreement Levelmentioning
confidence: 62%
“…In this review, the efficacy of concomitant therapy was found to be duration dependent, with 10‐day concomitant therapy being the most efficacious therapy and superior to 10‐day sequential therapy. Concomitant therapy also showed superior efficacy for metronidazole‐resistant strains and metronidazole plus clarithromycin‐resistant strains . A study from Israel suggested better compliance and fewer adverse effects with sequential treatment when used as a second‐line regimen, which they found noninferior to bismuth‐based quadruple therapy …”
Section: Sequential and Concomitant Therapymentioning
confidence: 99%
“…Concomitant therapy also showed superior efficacy for metronidazole-resistant strains and metronidazole plus clarithromycin-resistant strains. 73 A study from Israel suggested better compliance and fewer adverse effects with sequential treatment when used as a second-line regimen, which they found noninferior to bismuth-based quadruple therapy. 74 A 5-year prospective review in Italy assessed antimicrobial resistance to clarithromycin, metronidazole, and levofloxacin before giving 10-day sequential therapy as first-line therapy.…”
Section: S Equential and Con Comitant Ther Apymentioning
confidence: 99%
“…When conventional and novel strategies are considered, medical technology solutions are emerging in response to the AMR challenge. Literature reports show that concomitant medication with different antibiotics provides better efficacy in the eradication of bacterial infections compared to sequential or hybrid therapies 103,104. However, the current strategies have reframed from using antibiotics, and therefore, the researchers have a tendency to combine medical technologies for diagnosis, prevention, and therapy in combating bacterial infections.…”
Section: Introductionmentioning
confidence: 99%